Angola : Sixth Review Under the Stand-By Arrangement, Request for Waivers of Nonobservance of Performance Criteria, and Proposal for Post-Program Monitoring: Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Angola. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This report discusses Angola's sixth review under the Stand-By Arrangement (SBA) and request for waivers of nonobservance of performance criteria. Three years after the abrupt decline in world oil prices that severely impacted its economy, Angola has reached a sharply improved fiscal position, a more comfortable level of net international reserves, and a stable exchange rate. The authorities have embarked on far-reaching institutional reforms to enhance accountability in public spending and predictability in oil revenue transfers.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet